AHMAD WAHID DAN PENGKRITIKNYA: AHMAD WAHIB AND HIS CRITIQUES - Ahmad Nabil Amir; Tasnim Abdul Rahman, (Jurnal Pengajian Melayu (JOMAS), 2025)
ABSTRAK Makalah ini meninjau pemikiran Ahmad Wahib (1942–1973) serta reaksi pengkritiknya dalam kalangan puak konservatif dan ortodoks di Indonesia. Isu utama yang diketengahkan ialah bentuk kritikan yang dilontarkan terhadap gagasan pembaharuan Islam yang dibawa oleh Wahib, yang sering dianggap bertentangan dengan pandangan arus perdana. Kajian ini menganalisis pergulatan idea Wahib berhubung isu keagamaan, sosial, dan pengalaman hidupnya dalam masyarakat majmuk Indonesia. Penelitian ini menelusuri catatan harian Ahmad Wahib yang memaparkan pandangan beliau tentang etika, hukum, sastera, politik dan sosial. Catatan tersebut memperlihatkan ketajaman pemikiran Wahib sebagai intelektual muda yang kritis terhadap kejumudan beragama dan menyeru kepada tafsiran Islam yang lebih rasional serta kontekstual. Kajian ini menggunakan pendekatan kualitatif berbentuk penelitian kepustakaan dan dokumentari, dengan analisis deskriptif, komparatif, historis dan analitis terhadap karya-karya Wahib dan tulisan yang berkaitan dengan pemikiran serta kritik sosialnya. Hasil kajian merumuskan bahawa Ahmad Wahib ialah tokoh reformis Islam moderat yang menekankan nilai kebebasan, rasionalisme, dan kemanusiaan. Pemikirannya membuka ruang kepada perbincangan baharu dalam wacana Islam moden di Indonesia. Kajian lanjutan disarankan untuk meneliti perbandingan pemikiran Wahib dengan tokoh seperti Nurcholish Madjid dan Harun Nasution, serta pengaruhnya terhadap generasi muda Islam kontemporari. Pendekatan interdisiplin yang menggabungkan falsafah, sosiologi agama dan hermeneutik moden juga dicadangkan bagi memperluas pemahaman terhadap dimensi kemanusiaan dalam gagasan Wahib. Kata kunci: Ahmad Wahib; kritik; pemikiran; pembaharuan; Himpunan Mahasiswa Islam (HMI) Abstract This paper examines the thoughts of Ahmad Wahib (1942–1973) and the reactions of his critics among conservative and orthodox groups in Indonesia. The main issue highlighted is the nature of the criticisms directed at Wahib’s ideas of Islamic reform, which were often perceived as opposing mainstream religious views. The study analyses Wahib’s intellectual struggles concerning religious and social issues, as well as his experiences living within Indonesia’s pluralistic society. The research traces Ahmad Wahib’s personal journals, which reveal his views on ethics, law, literature, politics, and society. These writings demonstrate Wahib’s intellectual sharpness as a young thinker who was critical of religious rigidity and who advocated a more rational and contextual interpretation of Islam. The study employs a qualitative approach based on library and documentary research, using descriptive, comparative, historical, and analytical methods to examine Wahib’s works and other writings related to his social thoughts and critiques. The findings conclude that Ahmad Wahib was a moderate Islamic reformist who emphasized the values of freedom, rationalism, and humanism. His ideas opened new spaces for discussion within the discourse of modern Islam in Indonesia. Further research is recommended to compare Wahib’s ideas with those of figures such as Nurcholish Madjid and Harun Nasution, as well as to explore his influence on the younger generation of contemporary Muslims. An interdisciplinary approach combining philosophy, sociology of religion, and modern hermeneutics is also suggested to deepen understanding of the humanistic dimensions in Wahib’s intellectual framework. Keywords: Ahmad Wahib; critique; thought; reform; Himpunan Mahasiswa Islam (HMI)